A Study The Software Development Kit (SDK) Architecture For Payment Gateway Service On The Internet: Developing a Streamlined Software Development Kit (SDK) Architecture for Payment Gateway Service on the Internet (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Payment Card Industry Data Security Standard (PCI DSS)certification makes Solinor the firstsoftware company in Finland. A primary motivation for this thesis research was Solinor's need tostreamline the process of deploying integrating the Payment Highway product. With a well-thought-outSoftware Development Kit that is simple to use and understand, the Payment Highway may be built morequickly for a client's unique project. Research analysis of the Payment Highway product followed thepresent state analysis to illuminate the needs of the SDK. After collecting comprehending user needs,the Software Development Kit's architecture and design were developed. The study's last stage involvedthe creation distribution of the SDK for developers.